Upgrade Learning Manajemen Sistem di Era 4.0 dalam Menunjang Sarana dan Prasarana di Sekolah Studi Kasus di SMK Nurul Hikmah Sangatta - Muhammad Ibnu Faruk Fauzi; Halimatus Sa’diyah (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Technology's advancement and expansion continue to make it more powerful and smart. Along with the industrial era 4.0 that we are now experiencing. The advancement of this technology has an impact on the field of education. Both are connected to the infrastructure required to provide technologically sophisticated services to parents, instructors and students. At the moment, the world's education is educating future generations who must be technologically sophisticated at this time and in the future, which is full of extremely quick changes, there are demands for openness and, most importantly, greater competency. The findings of this research and analysis may be used to describe how a school responds to and follows technological advancements, as well as what The outcomes are favorable for schools, instructors, parents and children.